2009
DOI: 10.1124/jpet.109.158402
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Mediates the Sex Difference in Capsaicin-Induced Nociception in Rats

Abstract: We have previously shown that the male sex steroid testosterone inhibits slightly, but the female sex steroid 17␤-estradiol (E 2 ) potentiates dramatically, the capsaicin receptor-mediated current in rat dorsal root ganglion (DRG) neurons. Here, we used pharmacological methods and the nociceptive behavioral test to determine whether there is a sex difference in capsaicininduced acute pain in rats in vivo and what mechanism underlies this sex difference. Results revealed that intradermal injection of capsaicin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 39 publications
5
50
1
9
Order By: Relevance
“…Previous study results have led to contradictive conclusions. Research results have reported stronger antinociceptive action of morphine in the pro-oestrus and dioestrus phases as compared to the oestrus phase (hot plate test at 50°C) [22], increased pain sensitivity in the metoestrus and dioestrus phase as compared to pro-oestrus and oestrus phases, that is in phases characterized by low sex hormone levels (hot tail and tail immersion tests) [23], and much higher nociceptive action after administration of capsaicin s.c. in the pro-oestrus as compared to the oestrus phase (chemical pain stimulus) [24]. These contradicting results could be caused by a number of factors.…”
Section: Discussioncontrasting
confidence: 40%
“…Previous study results have led to contradictive conclusions. Research results have reported stronger antinociceptive action of morphine in the pro-oestrus and dioestrus phases as compared to the oestrus phase (hot plate test at 50°C) [22], increased pain sensitivity in the metoestrus and dioestrus phase as compared to pro-oestrus and oestrus phases, that is in phases characterized by low sex hormone levels (hot tail and tail immersion tests) [23], and much higher nociceptive action after administration of capsaicin s.c. in the pro-oestrus as compared to the oestrus phase (chemical pain stimulus) [24]. These contradicting results could be caused by a number of factors.…”
Section: Discussioncontrasting
confidence: 40%
“…capsaicin. The number of flinches and the time spent licking or lifting (s) the affected hindpaw were combined and reported as the number of nociceptive responses, where 1 s of licking/lifting is equal to one flinch response [1;49;78]. Sham injections consisted of capsaicin vehicle as a control.…”
Section: Methodsmentioning
confidence: 99%
“…45 Importantly, TRPV1-induced changes in current were not assessed in either of these studies as neither was the phosphorylation status of TRPV1. Separately, increased capsaicininduced nociception was apparent in female rats compared with male rats, 46 a response that was shown to be independent of PKA activity. The apparently conflicting findings in these studies may be a reflection of differences in the concentrations of the estrogens used, and further investigation of the impact of sex hormones, both male and female, on the vascular effects of TRPV1 is warranted.…”
Section: 32mentioning
confidence: 99%